Fat rather than health – Ecotoxic responses of Bufo raddei to environmental heavy metal stress during the non-breeding season - Wenya Zhang; Hao Sun; Rui Su; Shengnan Wang (Ecotoxicology and Environmental Safety, 2022)
The non-breeding season is a critical period for iteroparous animals to repair damage and store energy, which is crucial for future survival and reproductive success. However, it is unknown how animals allocate energy efficiently among reproduction, self-maintenance, and repair of oxidative damage caused by breeding during the non-breeding period, particularly under pollution. In the present study, the self-maintenance response and reproductive strategy of Bufo raddei to long-term environmental heavy metal stress was explored during the non-breeding season. Heavy metal enrichment level, organ coefficients, nutritional status, gonadal developmental level, oxidation level, and the immune status of B. raddei during the non-breeding season were tested, energy allocation preferences and energy consumption costs were analyzed. The results revealed significant heavy metal accumulation through biomagnification in the organs of B. raddei from the polluted area. Under long-term environmental heavy metal pollution, the energy investment by B. raddei for growth and energy storage was higher than that for health-maintenance during the early life cycle stage. The energy inputted for immune and antioxidant functions was significantly lower, and the energy inputted for self-maintenance during the early life stage was significantly higher than that during the late stage. B. raddei from a heavy metal polluted area spent more energy consumption cost on immunity and oxidative stress, but suffered higher oxidative stress and lower immune status. Moreover, the reproductive input of individuals in a heavy metal polluted area was generally low during the non-breeding season, and the energy input for reproduction limited the energy input for self-maintenance in females.